Informative Function in the Contents of Preachers’ Sermons in Jayapura Churches - Kabanga', Lewi; Wenda, Daniel; Labobar, Maryo Welly (ELS Journal on Interdisciplinary Studies in Humanities, 2022)
Informative function has function to represents one’s understanding of fact and knowledge, to communicate information, and to deliver message. In sermons’ preachers in GKI churches of Jayapura give view that language in theological context can be elaborated with local education/wisdom in Sentani. This study tries to figure out micro function of informative function used by the preacher in educating their congregation. The method used in this study was descriptive qualitative with the technique of recording. The data was transcribed and then reduced. The reduction data then was indexed into table as data displayed. The analysis of data was done based on the elements and features of language used in informative function. The results show that the micro functions of informative function used by the preachers are to give advice, to lecture, to announce, and to give opinion. These micro functions are framed in true values, facts, and historical traces. Further action is also facilitated by the level of acceptance or understanding among the congregations. The acceptance is proved by four elements such as language use, context, point of discussion, and attitude. Fortunately these four elements show the positive respond by the congregations.